Characteristic Analysis of Horizontal Axis Wind Turbine Using Airfoil NACA 4712 - Susilo, Bili Darnanto; Jatisukamto, Gaguk; Kustanto, Muh Nurkoyim (Journal of Mechanical Engineering Science and Technology (JMEST), 2019)
Wind energy has been developed and used as a source of electrical energy by converting wind energy into electrical energy using a generator. There are some wind turbine parameters that important for wind turbines design and model, includes the size of the rotor radius, airfoil selection, chord length, and pitch angle. The study aims to characterize the performance of a horizontal axis wind turbine using computational methods. The methods used a design and simulation of NACA 4412 and NACA 4712 airfoil using QBlade software using wind conditions in the region of Pancer, Jember.  Results show that the maximum Cl value of NACA 4712 is higher than in NACA 4412. NACA 4712 has a maximum Cl value = 1.696 at α = 14o while NACA 4412 airfoil has a maximum value of Cl = 1.628 at α = 15o. NACA 4712 has the maximum value of Cl/Cd = 153 at α = 2o , while the NACA 4412 has a maximum value of Cl/Cd = 133.5 at α = 5.5o. The maximum value of Cl/Cd 4712 is higher than the NACA 4412. At 7.66 m/s of wind speed with 10% turbulence conditions, wind turbines with NACA 4712 airfoil have Cp turbine performance parameters of 0.49929 and obtain a power of 1.15 kW, while wind turbines with NACA 4412 have Cp turbine performance parameters of 0.395365 and obtained power of 0.889 kW at the same wind speed.